2007
DOI: 10.1051/0004-6361:20078082
|View full text |Cite
|
Sign up to set email alerts
|

Atomic data for radioactive elements Ra I, Ra II, Ac I and Ac II and application to their detection in HD 101065 and HR 465

Abstract: Radiative data for transitions of astrophysical interest in radioactive elements Ra I, Ra II, Ac I and Ac II have been computed using a semi-empirical relativistic Hartree-Fock approach including core polarization effects. Most of the oscillator strengths reported in the present paper are new. A possible detection of radium (Ra II) and actinium (Ac II) in the spectrum of the stars HD 101065 and HR 465 is examined and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 38 publications
1
30
0
4
Order By: Relevance
“…Moreover, in this work core-valence correlation contributions show that excitations energies are have not as yet converged compared with valence-valence correlations. A contribution to excitation energies from including ; the values for wavelengths in this web site were often compiled from [37]) d Quinet [18] 5f orbital is expected because it had been found that the energies of low-lying levels in lanthanum, which have open shells much like actinium, were improved with a configuration set that included the 4f orbital [25]. We note though that level structure data for actinium is nearly nonexistent in the literature; we need further theoretical or experimental results for better comparison.…”
Section: Energy Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in this work core-valence correlation contributions show that excitations energies are have not as yet converged compared with valence-valence correlations. A contribution to excitation energies from including ; the values for wavelengths in this web site were often compiled from [37]) d Quinet [18] 5f orbital is expected because it had been found that the energies of low-lying levels in lanthanum, which have open shells much like actinium, were improved with a configuration set that included the 4f orbital [25]. We note though that level structure data for actinium is nearly nonexistent in the literature; we need further theoretical or experimental results for better comparison.…”
Section: Energy Levelsmentioning
confidence: 99%
“…Radiative data for astrophysical interest in radioactive element Ac was computed using a semi-empirical relativistic Hartree-Fock approach including core polarization effects. A possible detection of actinium in the spectrum of the stars HD 101065 and HD 465 was examined and discussed [18].…”
Section: Introductionmentioning
confidence: 99%
“…This study is an extension of our previous theoretical works dedicated to the atomic properties of some other short-lived radioelements such as technecium (Z¼43) [15], promethium (Z¼61) [16], francium (Z¼87) [17], radium (Z¼88) [18], actinium (Z¼89) [18] and americium (Z¼95) [19].…”
Section: Introductionmentioning
confidence: 99%
“…In Table X intensity, observed wavelengths of the transitions, uncertainty of the observed wavelengths, observed wavenumbers, uncertainty of the observed wavenumbers, the corresponding lower and upper levels, line reference (Column 8), transition rates, uncertainty of the transition rates and the reference for the transition rates (Column 11) are given. Theoretical estimates of energy levels and dipole matrix elements for singly ionized Ra have been reported 32,51,57,58 . Here we present the transition rates from Sahoo et al 32 as the uncertainty was given for the calculated values.…”
Section: Ra IImentioning
confidence: 99%